The Unfading Eros of Love in the Latest Poetry by Kornelijus Platelis - Jakaitė, Dalia (Literatūra, 2019)
The object of this article is the eros of love in the latest poetry by K. Platelis: books Palimpsestai (2004) and Įtrūkusios mėnesienos (2018). Theoretical-methodological scope – phenomenology; the main references – M. Merleau-Ponty and E. Levinas. The phenomenology, reflecting eros subjectivity, corporeality, time and space, allows for more actualization and understanding of the phenomenon of the eros of love. It suggests new categories through which individual and subjective poetic meanings come through. Love and its eros is one of the dominants in works of poets of K. Platelis’ generation. This phenomenon, related not only to the experiences of love, but also to the experiences of death, encompassing not only individuals, but also things, in works of this author gets into the complex cultural, historical, mythological context, grows out of this context and gives it a distinct poetic form. The hunger of eros (eros as a hunger), set up at the beginning of the article, and its analysis allow a better understanding of the otherness of mythopoetic transformations typical to K. Platelis’ poetry, as well as the dynamics of the eros of love and death, the interaction of eros of different times, reality and its simulation, the connection between passion and the world of things. Time, as one of the most important phenomena in the eros world, makes it possible to feel the particular dynamics of eros, a certain rhythm based on contradictions and ambiguities, and refers to the dynamics of the roles of different subjects in the eros situation. One of the main phenomena in the latest poetry is the middle aged eros, characterized by the autoironic rehabilitation of eros. Poems of Platelis have a distinctly erotic space. From the wide spectrum of the spatial eros imagination, it is worth highlighting its cultural aspect. It is necessary for identifying intersubjective relations, emotional and material experiences of eros. The eros, arising from the subjective observation of space and its objects, is characterized by the tension of a real and simulated world, metaphysical and concrete physical reality.
Keywords: Kornelijus Platelis; eros; love; phenomenology; myth; space; time; hunger